A measurement tool to explore customer willingness to use the MyTelkomsel Super App through expected service synergies - Muharlis Muharlis; Indrawati Indrawati (International Journal of Accounting and Management Information Systems, 2025)
Purpose: The adoption of Super Apps in the digital service landscape has become increasingly prevalent, yet limited studies have explored the factors influencing users’ willingness to use the Super App. This research aims to address this gap by developing a valid and reliable measurement tool to assess the determinants of customer willingness to use the MyTelkomsel Super App through Expected Service Synergies as the mediating variable. Research/methodology: Drawing upon the framework by Fang, Liao, and Li (2024), the study incorporates established constructs such as Perceived External Prestige, Brand Competence, Complementarity, Compatibility, and Perceived Fit. A key modification involves the addition of Trust to enhance the model's explanatory power. A pilot test, involving 30 MyTelkomsel users, was conducted to evaluate the instrument's validity and reliability using Corrected Item-Total Correlation and Cronbach’s Alpha. Results: The results confirm that all 14 constructs and 48 items meet the criteria for Corrected Item-Total Correlation and Cronbach’s Alpha, indicating that this measurement is deemed suitable for future large-scale empirical research. Conclusions: This study successfully develops a reliable and valid measurement tool for assessing customer willingness to use the MyTelkomsel Super App, with Expected Service Synergies serving as a mediating variable. Limitations: This study is limited to pilot testing involving only 30 users, which may affect the generalizability of the results. Contribution: The research contributes to the literature by introducing an extended measurement model tailored to Super App contexts, supporting future empirical studies and practical implementation in digital service development.